Improving legal knowledge about marriage and limitation of marriage in Integrated Islamic High Schools Al Fityan Medan - Harianto, Dedi; Maharany, Utary; Mulhadi; Lubis, Rafiqoh; Yusrin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
According to the central Bureau of statistical report, early marriage among the younger generation in Indonesia shows symptoms of improvement. This is a violation of marital law provisions and the potential to cause negative impacts in form of divorce and an increase in marital mortality during childbirth. To overcome these problems, it is necessary to provide additional legal knowledge to students in the form of legal counseling, question and answer, and discussion of marital law and marital age limits, as well as the donation of marriage law books. Based on the results of the evaluation, it was concluded that there was an increase in student knowledge about marital law and marital age limits, refers to the analysis of the questions asked by students in the question and answer session, as well as a summary of the results of group discussion submitted by representative of each group.